2004
DOI: 10.1007/s00429-004-0439-5
|View full text |Cite
|
Sign up to set email alerts
|

The thymus is a site of mast cell development in chicken embryos

Abstract: Thymic mast cells were studied by light and transmission electron microscopy in chicken embryos during organogenesis. Mast cells made their first appearance at day 15. At days 16 and 17, there was a burst of mast cell development with a peak of 278 +/- 54 cells/mm(2) at day 16. Then, mast cell density decreased until hatching. During the whole embryonic period, about 80% of mast cells localized to the thymic medulla. In the cortex, they were less numerous, and some rare mast cells could be identified in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…In our study on chicken, the number of mast cells was higher in the thymic medulla than in the cortex of the thymus, although they might vary with age. These results are in parallel with the findings of Crivellato et al. (2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study on chicken, the number of mast cells was higher in the thymic medulla than in the cortex of the thymus, although they might vary with age. These results are in parallel with the findings of Crivellato et al. (2005).…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted on chicken embryos, the highest number of MCs were found in 16 and 17‐day‐old chickens, with 80% of Mcs located in the thymic medulla. The same study also showed that the number of mast cells in the cortex, capsule and septa was less than that observed in the thymic medulla (Crivellato et al., 2005). In our study on chicken, the number of mast cells was higher in the thymic medulla than in the cortex of the thymus, although they might vary with age.…”
Section: Discussionmentioning
confidence: 66%
“…In normal thymus of humans and other animal species, MCs are localized in the capsule and along the connective tissue septa within the gland (Wight 1970; Frazier 1973; Kendall & Warley 1986). The presence of MCs precursors in thymus was first reported by Ginsburg and Sachs (1963) and further studies supported the possible involvement of MCs in thymus organogenesis (Crivellato et al. 2005) and the influence of removal or stimulation of thymus on the number of tissue MCs distant from the thymic lymphoid tissue (Rao 1972).…”
Section: Discussionsupporting
confidence: 52%
“…The T cell marker Thy-1 identifies mast cell precursors in fetal blood, as Thy-1 lo c-Kit hi cells displayed mast cell potential in contrast to their Thy-1 − c-Kit + counterpart 32 . More recently, the thymus has been identified as a site of mast cell development in chicken embryos 33 . Mast cells have also been reported in human thymuses in pathological cases 34,35 , and are seen in medullary regions which are poor in Delta-class Notch ligands 36,37 .…”
Section: Discussionmentioning
confidence: 99%